Experimental investigation on seismic performance of plain engineered cementitious composite beams - Tian, Likang; Tan, Yan; Wei, Xiao-Xiao; Ouyang, Li-Jun; Xu, Ran; Yu, Jiang-Tao (Frontiers in Materials, 2022)
The authors proposed to use plain engineered cementitious composites (ECC) in construction without aligned reinforcement. In this study, ECC with tensile strain capacity up to 10% was produced, which has the comparable deformability level as steel reinforcement. To demonstrate the feasibility of plain ECC construction, 5 plain ECC beams and 2 steel reinforced concrete reference beams were prepared and four-point bending reversed cyclic loading tests were conducted to the beam specimens. The experimental tests indicated that the plain ECC beams showed more stable hysteresis loops with improved energy dissipation capacity, deformation restoring capacity and lower stiffness degradations, as compared with normal RC beams. Two categories of failure modes were observed, i.e., flexural failure mode and shear failure mode. With the increase of the shear span ratio, the failure mode of ECC beams changed from shear failure to flexural failure. Additionally, the increase in sectional dimension had a positive inﬂuence on the stiffness and energy dissipation capacity of ECC beams. It is experimentally verified that the plain ECC beams has sufficient load bearing capacity under static and seismic loading.